Characterization of a waterhemp (Amaranthus tuberculatus) population from Illinois resistant to herbicides from five site-of-action groups. (June 2019) - Evans, Cody M.; Strom, Seth A.; Riechers, Dean E.; Davis, Adam S.; Tranel, Patrick J.; Hager, Aaron G.
Abstract: Experiments were initiated to characterize a waterhemp population (CHR) discovered in a central Illinois corn field after it was not controlled by the 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor topramezone. Field experiments conducted during 2014–2015 indicated that acetolactate synthase (ALS)-, protoporphyrinogen oxidase (PPO)-, photosystem II (PSII)-, and HPPD-inhibiting herbicides and the synthetic auxin 2, 4-D did not control the CHR population. Laboratory experiments confirmed target site–based resistance mechanisms to ALS- and PPO-inhibiting herbicides. Herbicide doses required to reduce dry biomass 50% (GR50 ) were determined in greenhouse dose–response experiments, and indicated 16-fold resistance to the HPPD inhibitor mesotrione, 9.5-fold resistance to the synthetic auxin 2, 4-D, and 252-fold resistance to the PSII inhibitor atrazine. Complementary results from field, laboratory, and greenhouse investigations indicate that the CHR population has evolved resistance to herbicides from five sites of action (SOAs): ALS-, PPO-, PSII-, and HPPD-inhibiting herbicides and 2, 4-D. Herbicide use history for the field in which CHR was discovered indicates no previous use of 2, 4-D.